Affective Evaluations of Exercising: The Role of Automatic-Reflective Evaluation Discrepancy - Brand, Ralf; Antoniewicz, Franziska (Journal of sport & exercise psychology, 2016)
Sometimes our automatic evaluations do not correspond well with those we can reflect on and articulate. We present a novel approach to the assessment of automatic and reflective affective evaluations of exercising. Based on the assumptions of the associative-propositional processes in evaluation model, we measured participants' automatic evaluations of exercise and then shared this information with them, asked them to reflect on it and rate eventual discrepancy between their reflective evaluation and the assessment of their automatic evaluation. We found that mismatch between self-reported ideal exercise frequency and actual exercise frequency over the previous 14 weeks could be regressed on the discrepancy between a relatively negative automatic and a more positive reflective evaluation. This study illustrates the potential of a dual-process approach to the measurement of evaluative responses and suggests that mistrusting one's negative spontaneous reaction to exercise and asserting a very positive reflective evaluation instead leads to the adoption of inflated exercise goals.